Development of complement C5a and its receptor in malignant tumour cells as mammary tumour biomarker - Ganti, Norhaifa (2015)
Mammary cancer is the most common disease among women and second cause of female mortality related to cancer. The relationship between immune system and mammary cancer is still questionable. C5a is an important chemotactic protein that is recognized as an anaphylatoxin and chemoattractant that exerts proinflammatory actions in many pathological states. The complement C5a and its receptor are believed to be involved in development of mammary tumour due to its inflammatory properties. This study investigates the role of complement 5a (C5a) on mouse mammary cancer development by using malignant mouse mammary tumour cell line; 4T1. The expression of C5a/C5aR was determined by using Immunofluorescence staining and Reverse-Transcriptase PCR (RT PCR) and subsequently with Real Time PCR (qPCR) to measure the magnitude of C5a/C5aR expression. 40 specific pathogen free (SPF) Balb/c mice were randomly divided into four treatment groups. Each mouse was injected subcutaneously with 1x106 cells/ml into the mammary fat pad and treatments were given in the same manner. The liver samples were used for further analysis to validate the use of C5a and its receptor as mammary tumour biomarker by using Enzyme-linked Immunosorbent Assay (ELISA) and qPCR. The Immunofluorescence staining showed the green colour surrounding the blue colour of nucleus. The green colour indicates the presence of C5a receptor in the membrane of 4T1 cell line. Meanwhile, the Reverse Transcriptase PCR technique gave an intense single band in the agarose gel when viewed under gel documentation machine. These collective results proved that there are expression of C5a and its receptor in the malignant mammary tumour cell line; 4T1. The result for in-vitro studies showed that the PMX205 peptide gave lower percentage of cell viability than EP54 peptide when compared to the control group for each time line. The trend of the cell viability values was consistent and showed a significant result. This indicates that this peptide is capable to regress and kill these tumour cells. Meanwhile, qPCR technique showed that the magnitude of C5a and its receptor in PMX 205 treated group was lower than EP54 treated group and the magnitude of C5a and its receptor in normal tissue were significantly lower compared to its magnitude in tumour tissue. The consistency of in-vitro and in-vivo results strengthens the arguments regarding the involvement of C5a and its receptor in the development of malignant mammary cancer. The findings in this study showed that there is a functional relationship between C5a and the development of mammary tumour which suggested that C5a and its receptor can be used as mammary tumour biomarkers and C5a antagonist peptide (PMX205) has a potential in treating and preventing development of mammary tumour by blocking the receptor of C5a and inhibits the binding of C5a to its receptor. However, further studies are required to validate these findings including the exact role of C5a and its mechanism in malignant mammary tumour development and the potential of C5a as mammary tumour biomarkers.